Applying Results-Based Financing in Water Investments - Rodriguez, Diego; Suardi, Mario; Ham, Marcel; Mimmi, Luisa; Goksu, Amanda (World Bank, Washington, DC, 2014)
Given the broad array of issues and the complexity faced by the water sector as a whole (from irrigation to flood protection, to water conservation and hydropower), there is great demand for future exploring the potential of RBF and tackling the questions still unanswered about many of its operational dimensions. This document takes a closer look at some of the practical aspects of implementing various RBF water schemes. Chapter 2 provides an analytical framework to explore if and when RBF can be a viable option, shedding light on some key factors and preconditions that are necessary for RBF to work--with the understanding that it can be used either as an alternative or a complement to a more traditional input-based funding scheme. Chapter 3 then revisits the concepts discussed in the analytical framework through the analysis of various case studies of RBF approaches in different water-related areas. Some of the case studies are based on actual projects already implemented or ongoing, while others are an illustrative elaboration, given the lack of practical cases to use as sources. Chapter 4 presents some conclusions and lessons learned. The key challenges that are likely to be encountered in designing an RBF scheme deal with: the clarity and level of certainty of the relationships from input to output to outcomes (causal links); the ease and availability of measurable indicators; and, consequently, the optimal determination of the necessary incentive(s) to align the goals of the principal with the agents' deliverables. Appendix A presents a glossary of RBF concepts and acronyms. Appendix B presents specific results and indicators which may be relevant for different sectors.